The Legitimacy of Prohibiting Euthanasia - Gildenhuys, Peter (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2015)
John Arras argues against the legalization of physician-assisted suicide and active euthanasia on the basis of social costs that he anticipates will result from legalization. Arras believes that the legalization of highly restricted physician-assisted suicide will result in the legalization of active euthanasia without special restrictions, a prediction I grant for the sake of argument. Arras further anticipates that the practices of physician-assisted suicide and euthanasia will be abused, so that many patients who engage in these practices will lose out as a result. He refers to these losses as social costs to legalization. But the social costs at play in typical public policy debates are borne by individuals other than the agent who engages in the controversial activity, specifically by people who cannot be held responsible for enduring those costs. Even if plausible interpretations of Arras’ predictions about the abuse of the practice are granted, legalization of physician-assisted suicide or euthanasia brings no social costs of this latter sort. For this reason, and also because a ban on euthanasia is unfair to those who would profit from it, the losses in utility brought about by legalization would have to be very great to justify a ban.